2022
DOI: 10.1021/acs.analchem.1c04406
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Two-Dimensional Fluorescent Covalent Organic Framework Nanosheets for the Detection and Removal of Nitrophenols

Abstract: In this work, we synthesized a two-dimensional fluorescent covalent–organic framework (TFPB–TTA COF) nanosheet by selecting and designing reactive monomers to realize the dual-functional processing of nitrophenols. The staggered benzene ring, triazine structure, and imine bond (CN) of the TFPB–TTA COF can capture free nitrophenols through hydrogen bonding and conjugation interaction, and then, the photoinduced electron transfer and fluorescence resonance energy transfer (FRET) between the TFPB–TTA COF and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…This result is consistent with the PXRD result of CHOF-1 after being soaked in acidic and basic solutions. On the other hand, the linear conjugation polymers (named COP-1) in the crystal structure of CHOF-1 cannot be decomposed due to the chemical stability of Schiff base under the environment of 4-NP, TNP, HCl, and NaOH at low concentrations. , Therefore, the fluorescence spectra of CHOF-1 after its crystal structure were destroyed by NaOH solution (pH = 10) and then respective additions of 4-NP and TNP were measured, as shown in Figure S17. It is found that not only does the fluorescence spectrum of COP-1 match well with that of CHOF-1 but also the fluorescence spectra of COP-1 after the additions of 4-NP and TNP are consistent with those of CHOF-1 upon the addition of 4-NP and TNP.…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with the PXRD result of CHOF-1 after being soaked in acidic and basic solutions. On the other hand, the linear conjugation polymers (named COP-1) in the crystal structure of CHOF-1 cannot be decomposed due to the chemical stability of Schiff base under the environment of 4-NP, TNP, HCl, and NaOH at low concentrations. , Therefore, the fluorescence spectra of CHOF-1 after its crystal structure were destroyed by NaOH solution (pH = 10) and then respective additions of 4-NP and TNP were measured, as shown in Figure S17. It is found that not only does the fluorescence spectrum of COP-1 match well with that of CHOF-1 but also the fluorescence spectra of COP-1 after the additions of 4-NP and TNP are consistent with those of CHOF-1 upon the addition of 4-NP and TNP.…”
Section: Resultsmentioning
confidence: 99%
“…Since the groundbreaking research on covalent organic frameworks (COFs) reported by Yaghi et al, such type of popular crystalline materials have attracted extensive attention. COFs are constructed from organic ligands through covalent bonds and possess predesigned structures as well as precise customized functions that facilitate the implementation of chemical and structural control. Despite enormous attractive research on the design and construction of COFs having been conducted for nearly 20 years, there is still great potential for the development of luminescent COF materials. Notably, the natural π-conjugated structure of COFs is beneficial to study their luminescence performance, while the π–π stacked structure also causes aggregation-induced quenching (ACQ) and hinders the emission of COFs. , Meanwhile, weakening the stacking degree between layers will increase the intramolecular rotation, which is also a dilemma for luminescence. At present, fluorescent organic linkers with large conjugated structures or with an aggregation-induced luminescence effect are usually selected for the fabrication of luminescent COFs. Emissive COFs can also be obtained via postmodification or exfoliation. To improve the luminescence properties of COFs in an effective way, the emergence of luminescent composites based on COFs stands out from single COFs. As we know, even though luminescent COFs as emerging functional materials have been dramatically studied over the past few years, ,, research on directly growing COFs on the core substrate with a limited number of layers to improve the luminous efficiency still remains less understood.…”
Section: Introductionmentioning
confidence: 99%
“…COFs have stable networks and open channels, which are extraordinarily conducive to the transport of electrolyte ions and have great potential in various applications. It has been reported that some COFs or COF-based sensors have better performance [ 8 , 9 , 10 ]. However, COFs are highly conjugated, and the π–π interaction between layers would lead to a decrease in specific surface area and poor electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%